Flip bifurcation analysis and investigation of conjunctivitis virus by using sustainable control approach - Ahmad, Aqeel; Kulachi, Muhammad Owais; Aly, Ayman A.; İnç, Mustafa; Ahmad, M. O.; Rezapour, Shahram (Elsevier Sci Ltd, 2025)
The goal of this work is to investigate the early diagnosis and treatment of conjunctivitis viral infections in the eyes by introducing non-medication recovery strategies. To this end, a new mathematical model is developed for better control of conjunctivitis virus. The essential characteristics of an epidemic model bounded-ness and uniqueness are examined for bounded discoveries using Banach space. A recently built system, SEIRuRi, R u R i , is analyzed computationaly and quantitatively to find its stable position. The flip bifurcation of the proposed system has also been verified under different parameters impact. Using the next generation approach, we have generated the reproductive number R0and R 0 and confirmed its sensitivity analysis based on each parameter to determine how sensitive the rate of parameter change is in the proposed eye infection. The created system's solution is found utilizing the Atangana-Toufik technique, a sophisticated method for dependable bounded solution including error analysis, employing various fractional values. In order to confirm that those with strong immune systems were able to recover from acute stage infections without the need for medicine, simulations have been created to mimic the actual behavior and consequences of conjunctivitis virus infections. Due to the patients' strong immune systems and preventative measures, as well as early diagnosis for treatment and better control, we determine the actual state of the conjunctivitis virus control for both those receiving medicine and those who are not receiving medicine.
Keywords: Mathematical modeling; Bounded-ness; Uniqueness; Non-local kernel; Flip bifurcation; Atangana-Toufik